Hambatan Pemerintah Yaman dalam Mengelola Bantuan Pangan dari World Food Programme Tahun 2011-2016 - Swadevi, Wayan Yulia; Kumala Dewi, Putu Ratih; Suwecawangsa, Adi P. (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2018)
ABSTRACT This thesis examines the Yemeni government’s obstacles in managing food aid from World Food Programme in 2011-2016. The large amount of WFP aid that goes to Yemen is an interesting case because it’s not able to reduce the food crisis, instead the food crisis gradually increase in Yemen. The assistance provided by WFP to Yemen is quite large and able to accommodate the needs of people who are in emergency food crisis. However, the implementation of the aid when it arrived in Yemen encountered various constraints associated with the state resources so that aid programs could not realize significant results in reducing the food crisis. In this thesis, researcher examines the obstacles experienced by the Yemeni government in managing food aid from the World Food Programme. The framework of this thesis departs with the concept of Management of Foreign Aid with using the Paris Declaration on Aid Effectiveness procedure. Keywords: Obstacles, Foreign Aid, Yemeni Government, Paris Declaration